E-cigarettes, a safer alternative for teenagers? A UK focus group study of teenagers' views. Issue 11 (16th November 2016) - Hilton, Shona; Weishaar, Heide; Sweeting, Helen; Trevisan, Filippo; Katikireddi, Srinivasa Vittal
Abstract : Objective: Concerns exist that e-cigarettes may be a gateway to traditional cigarettes and/or (re)normalise teenage smoking. This qualitative study explores how teenagers in the UK currently perceive e-cigarettes and how and why they do or do not use them. Design: 16 focus groups were conducted across the UK between November 2014 and February 2015, with 83 teenagers aged 14–17. All discussions were digitally recorded, transcribed verbatim, imported into NVivo 10 and thematically analysed. Results: Teenagers generally agreed that e-cigarettes are useful products for smokers, including teenage smokers, to quit or reduce traditional cigarette use. Concerns were expressed about lack of information on their precise ingredients and any unknown risks for users and bystanders. However, teenagers typically viewed e-cigarettes as substantially less harmful than traditional cigarettes. They perceived e-cigarettes as attractive, with products described as 'fun' and having 'great flavourings'. Seeing websites or social media featuring e-cigarettes, especially YouTube 'vaping tricks', prompted some experimentation and imitation. E-cigarettes were used in a variety of situations, including at parties or when they could not smoke traditional cigarettes. A very few participants suggested covert use was a possibility and that e-cigarettes might help maintain a fledgling nicotine habit. Conclusions: Teenagers support the use of e-cigarettes as smoking cessation aids for established adult smokers. However, they engage with these products differently from adults, with the novel hypothesis that covert use could potentially reinforce traditional cigarette smoking requiring further investigation. Policy responses should more clearly meet the needs of young people, as well as helping established adult smokers.